Envisioning Future Urinary Tract Infection Diagnostics. (31st August 2021) - Patel, Robin; Polage, Christopher R; Dien Bard, Jennifer; May, Larissa; Lee, Francesca M; Fabre, Valeria; Hayden, Mary K; Doernberg, Sarah D B; Haake, David A; Trautner, Barbara W; Grigoryan, Larissa; Tsalik, Ephraim L; et al.
Abstract: Urinary tract infections (UTIs) are among the most common bacterial infections in the United States and are a major driver of antibiotic use, both appropriate and inappropriate, across healthcare settings. Novel UTI diagnostics are a strategy that might enable better UTI treatment. Members of the Antibacterial Resistance Leadership Group Laboratory Center and the Infectious Diseases Society of America Diagnostics Committee convened to envision ideal future UTI diagnostics, with a view towards improving delivery of healthcare, patient outcomes and experiences, and antibiotic use, addressing which types of UTI diagnostics are needed and how companies might approach development of novel UTI diagnostics. Abstract : Urinary tract infections are among the most common bacterial infections in the United States and are a major driver of antibiotic use, both appropriate and inappropriate, across healthcare settings.